2001
DOI: 10.4049/jimmunol.167.8.4286
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Extensive Pulmonary Metastases in Mice by Adoptive Transfer of Antigen-Specific CD8+ CTL Reactive Against Tumor Cells Expressing a Naturally Occurring Rejection Epitope

Abstract: In this study, we developed a mouse model of adoptive immunotherapy reflecting immune recognition of syngeneic tumor cells naturally expressing an endogenous rejection Ag. Specifically, in a pulmonary metastases model, we examined the potency and maintenance of an antitumor CD8+ CTL response in vivo, as well as its effectiveness against an “extensive” tumor burden. The approach taken was to first generate tumor-specific CTL from mice challenged with the CMS4 sarcoma coadministered with anti-CTLA4 mAb, which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 20 publications
1
49
0
Order By: Relevance
“…administration. CMS4-reactive CTL lines can be produced in mice (9) using an anti-CTLA4 mAb-based strategy (11,12). In vivo, we showed that the adoptive transfer of these CTL resulted in nearly complete regression of 3-day established experimental lung metastases, with half-maximal antitumor activity observed between 3-10 ϫ 10 4 CTL/mouse.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…administration. CMS4-reactive CTL lines can be produced in mice (9) using an anti-CTLA4 mAb-based strategy (11,12). In vivo, we showed that the adoptive transfer of these CTL resulted in nearly complete regression of 3-day established experimental lung metastases, with half-maximal antitumor activity observed between 3-10 ϫ 10 4 CTL/mouse.…”
mentioning
confidence: 86%
“…Furthermore, the potential relevance of the animal model would be further enriched if it were based on immune recognition of malignant cells naturally expressing tumor rejection Ag, as it would better mirror what occurs in human neoplasia. To that end, we have developed a syngeneic mouse model of CTL adoptive immunotherapy against experimental pulmonary metastases in both minimal (i.e., day 3 tumor-bearing mice) and extensive (day 10 tumor-bearing mice) disease settings (9). The model consisted of the CMS4 sarcoma, a solid tumor of BALB/c (H-2 d ) origin (10) that grows aggressively in naive, syngeneic hosts (9) either as an s.c. tumor or as a metastasis in the lung following i.v.…”
mentioning
confidence: 99%
“…26,27 Several vaccine strategies using HLA-A2-binding Her-2/neu CTL epitope peptide were reported to be safe and effective in eliciting CTL responses even in Her-2/neu-expressing cancer patients. 28,29 However, it is difficult to directly measure CTL activity in nonhuman primates, because little information is available on MHC class I-binding epitope peptide.…”
Section: Non-human Primate Study Against Human Her-2/neu H-j Ko Et Almentioning
confidence: 99%
“…Cells adhered within the first 5 min reached a maximum at 60 min [tumor vs. normal 20 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) vs. 1 (1-2)] and were elevated for the duration of the study period. Neither population adhered to the endothelium of the normal microcirculation.…”
Section: Adherent Cellsmentioning
confidence: 99%
“…3,[17][18][19] The effector cells used in adoptive cellular therapy range from ex vivo tumor-draining lymph node cells specifically or nonspecifically activated 20 to antigen-specific CTLs reactive to tumor cells naturally expressing appropriate peptide epitopes via MHC molecules. 21 CTLs mediating MHC-restricted tumor cell killing are particularly attractive as effector cells for adoptive therapy, with the therapeutic potency being governed by their binding affinity, number and specificity.…”
Section: Rolling and Flying Cellsmentioning
confidence: 99%